A comparative study to determine vitamin D status in type 2 diabetes and normal subjects in south India - Kumar, R. Anil; R, Lalitha; B. Shetty, Surekha (International Journal of Medical Research and Review, 2017)
Background: Vitamin D deficiency is common in general population in India in spite of adequate sunlight. We have decided to compare the prevalence of vitamin D deficiency in type 2 diabetes and normal individuals. Methods: 370 type 2 diabetes individuals attending Karnataka Institute of endocrinology and research outpatient department and 100 normal individuals were studied. Fasting plasma glucose, post prandial plasma glucose, lipid profile, vitamin D levels, BMI, waist circumference and BP of these subjects were measured. Results: Out of 370 type 2 diabetes subjects 67.3% were males and age group ranging from 21 to 80 years. Duration of diabetes vary from 0 to 20 years. Vitamin D deficiency was present in 83%, insufficiency in 13.8% and only 3.2% had normal vitamin D levels in type 2 diabetes. Vitamin D deficiency was common in individuals >50 years, males, BMI 25-30. Family history of diabetes was present in 60%. Hypertension was present in 47.6%. Total cholesterol, LDL, Triglycerides were lower and HDL levels were higher in type 2 diabetes individuals with vitamin D more than 20 nanograms per ml. In 100 normal individuals taken as controls 62% were males, age group ranging from 21 to 80 years. Vitamin D deficiency was present in 82% and insufficiency in 12% and 6% had normal vitamin D levels. Conclusions: Vitamin D deficiency was present in 83% of type 2 diabetes individuals and 82% of normal individuals. So both type2 diabetes and normal controls from south India are equally deficient in vitamin D. Total cholesterol, LDL, Triglycerides were lower and HDL levels were higher in type 2 diabetes individuals with vitamin D more than 20 nanograms per ml.